PENGARUH PENGGUNAAN APLIKASI EMIS 4.0 TERHADAP PENINGKATAN EFEKTIVIAS PENGELOLAAN DATA DI MADRASAH TSANAWIYAH SE-KECAMATAN MAJAULENG KABUPATEN WAJO - Siti Aminah; Nurhayati Makkarumpa; Sri Reski Ananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the Effect of the Use of EMIS 4.0 Application on the Effectiveness of Data Management in Islamic Education Institutions. This research is motivated by the digital era which requires educational institutions to adopt an effective and efficient information system in data management. This article reviews the effectiveness of the EMIS 4.0 application in program understanding, goal setting, timeliness, goal achievement, and real changes, as well as providing insight into decision-making methods in Islamic Education Institutions. This study uses quantitative research. The findings of this study show that the EMIS 4.0 application has an influence on the effectiveness of data management in Madrasah Tsanawiyah in Majauleng District, Wajo Regency.